Diagnóstico de uma área compactada por atividade minerária, na floresta amazônica, empregando métodos geoestatísticos à variável resistência mecânica à penetração do solo - Ribeiro, Admilson Írio; Longo, Regina Márcia [UNESP]; Teixeira Filho, Aristóteles; De Melo, Wanderley José [UNESP] (FapUNIFESP (SciELO), 2006)
A quite common problem in the recovery of degraded areas in the mineral exploration understands the compaction of the soil due to the intense traffic of machines and earth movement. The most common problem of the compaction of a degraded surface is: increase of the mechanical resistance to the penetration of the rooats, reduction of the aeration, alteration of the water flow and heat. Thus the present work had the basic objective of diagnosing the compaction of a degraded area by mining in a space way, through the mechanical resistance the way penetration to guide a future subsoiling in the place seeking recovery. Through the studies it was concluded that the kriging method in agreement with the space variation allows the division of the area studies in sub areas facilitating a future work to reduce cost and unnecessary interference to the atmosphere. The method was shown quite appropriate and it can be used in diagnosis of the compaction in a degraded area by mining, foreseeing subsoiling need.
Diagnosis of a compacted area by mining activity, in the Amazon forest, utilizing geoestatistic methods to the mechanical resistence variable to the penetration of the soil
Keywords: Compaction; Kriging; Space variability